The Kinship of Built Things - Coleman Coker (Oz, 1999)
As corporeal things we shape other things in ways that are constant with our being. Our activity on the earth as builders cause us to build; we as material things making other material things full of their own form, texture, smell, and structure, each standing on their own as things in the world.